Maintenance practices as a factor in the selection of materials for interior finishes and furniture - Magpantay, Vea Denise D.; Quevedo, Ma. Teresa P. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
To learn how Filipino homeowners consider maintenance practices in selecting materials for the home, this research examined the maintenance practices of selected Filipino households and how these practices influence their choice of materials for interior finishes and furnishings. Using an exploratory research design, ten (10) Filipino homeowners were purposely selected to participate in individual in-person or virtual interviews, with the latter conducted through Zoom or Messenger application. A material checklist was given to the participants before the interview and an interview guide with open-ended questions was used for the interview proper. For data analysis, an inductive and latent approach to reflexive thematic analysis was applied. Results show that the maintenance practices of the participants include sweeping, vacuuming, dusting, mopping, pagtatanggal ng agiw, repair, replacement, and refurbishment. The research found that participants only considered proactive maintenance when selecting interior finishes and furniture for the home, which involves selecting materials that are deemed durable and will last for a long time. The difficulties in maintenance encountered by the participants were due to the properties of the material they chose (e.g., floor color and pattern), the difficulty of the maintenance practice required (e.g., frequent mopping), the material being damaged by children and pets, and the increased floor area of some houses. Participants had the hardest and easiest time maintaining their floors and ceilings and furniture, respectively. Results also show that the participants consider maintenance relevant in material selection but in the form of choosing durable materials because it leads to increased productivity and time efficiency, decreased operational expenses, ensured health and safety of users, and extended operational lifespan of interior finishes and furniture of the home.
Thesis
Includes bibliographical references (pages 74-78)
Keywords: Home furnishings industry and trade -- Philippines; Dwellings -- Philippines. -- Maintenance and repair; Furniture design -- Philippines; Interior decoration -- Philippines; Home rehabilitation